Study of the physical properties of hydrogel films for low-temperature storage of microorganisms - Zubkov, Oleksandr; Trufanov, Oleh (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):246